Evolution of ethnic and urban women’s clothing of Slobozhanshchyna during the 20th century - Ilchuk, Vladislava (Art and Design, 2025)
The relevance of the current study is conditioned by the need for in-depth analysis and preservation of the cultural heritage of the region, since the interaction of traditional forms and influences of the urban environment on women’s clothing of Slobozhanshchyna during the twentieth century remains insufficiently investigated. The purpose was to comprehensively investigate the specifics of the evolution of ethnic and urban women’s clothing, its spatial characteristics and features of decoration on the territory of Slobozhanshchyna in the 20th century. The study used the following methods of scientific cognition: historical, cultural, and comparative historical analysis. The study provided a thorough description of the complex of traditional women’s clothing of Slobozhanshchyna, highlighting its typical elements, silhouette solutions, colouristics, and symbolism. Shirts, aprons, belts, hats, chest and upper elements of clothing, and typical embroidery ornaments and their compositional arrangement were analysed. The study also focused on the analysis of transformational processes in ethnic and urban women’s clothing of Slobozhanshchyna residents during the 20th century. Factors that contributed to the changes were analysed, in particular, the availability of factory fabrics, lifestyle modifications, the spread of urban fashion trends, and public policies regarding folk culture. A design project of the contemporary ethnocollection of women’s costume has been developed. The collection was based on a deep understanding of the architectonics, colouristics, and ornaments of traditional clothing of Slobozhanshchyna, adapting these elements to the requirements of contemporary fashion. The practical value of the study lies in the possibility of applying its results to integrate ethnic motifs into everyday and festive clothing. The results obtained serve as a basis for creating innovative design solutions that contribute to the popularisation and rethinking of the national cultural heritage.